Proteome analysis in thyroid pathology. (August 2015) - Pagni, Fabio; L'Imperio, Vincenzo; Bono, Francesca; Garancini, Mattia; Roversi, Gaia; De Sio, Gabriele; Galli, Manuel; Smith, Andrew James; Chinello, Clizia; Magni, Fulvio
<x xml:space="preserve">Abstract</x> The incidence of thyroid cancer has continuously increased due to its detection in the preclinical stage. Clinical research in thyroid pathology is focusing on the development of new diagnostic tools to improve the stratification of nodules that have biological, practical and economic consequences on the management of patients. Several clinical questions related to thyroid carcinoma remain open and the use of proteomic research in the hunt for new targets with potential diagnostic applications has an important role in the solutions. Many different proteomic approaches are used to investigate thyroid lesions, including mass spectrometry profiling and imaging technologies. These approaches have been applied to different human tissues (cytological specimens, frozen sections, formalin-fixed paraffin embedded tissue or Tissue Micro Arrays). Moreover, other specimens are used for biomarker discovery, such as cell lines and the secretome. Alternative approaches, such as metabolomics and lipidomics, are also used and integrated within proteomics.